2021
DOI: 10.1038/s41598-021-81500-4
|View full text |Cite
|
Sign up to set email alerts
|

TNFα promotes oral cancer growth, pain, and Schwann cell activation

Abstract: Oral cancer is very painful and impairs a patient’s ability to eat, talk, and drink. Mediators secreted from oral cancer can excite and sensitize sensory neurons inducing pain. Cancer mediators can also activate Schwann cells, the peripheral glia that regulates neuronal function and repair. The contribution of Schwann cells to oral cancer pain is unclear. We hypothesize that the oral cancer mediator TNFα activates Schwann cells, which further promotes cancer progression and pain. We demonstrate that TNFα is ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 65 publications
(153 reference statements)
0
44
0
Order By: Relevance
“…In the ovarian organoid model, prolonged TNF exposure confers precancerous phenotypes with high expression of cancer markers (43). TNF also induces the formation of cancer stem-like phenotypes in oral squamous cell carcinoma (44,45). Furthermore, TNF can directly stimulate breast cancer proliferation via the positive feedback loop of TNFR-1/NF-kB/STAT-3 (46) as well as be involved in cathepsin C-induced hepatocellular malignancy via MAPK signaling pathway (47).…”
Section: Cytokines In Tumor Growthmentioning
confidence: 99%
“…In the ovarian organoid model, prolonged TNF exposure confers precancerous phenotypes with high expression of cancer markers (43). TNF also induces the formation of cancer stem-like phenotypes in oral squamous cell carcinoma (44,45). Furthermore, TNF can directly stimulate breast cancer proliferation via the positive feedback loop of TNFR-1/NF-kB/STAT-3 (46) as well as be involved in cathepsin C-induced hepatocellular malignancy via MAPK signaling pathway (47).…”
Section: Cytokines In Tumor Growthmentioning
confidence: 99%
“…Glia are recognised as mediators of orofacial pain [ 91 , 92 ], and several studies suggest that SCs are involved in the increased nociception [ 58 , 59 ] and nerve invasion [ 60 , 61 ] observed in oral malignancies. One of the proposed mechanisms is the activation of SCs in response to tumour necrosis factor alpha (TNFα) secreted by OSCC cells.…”
Section: Schwann Cell Involvement In Physiology and Disorders Of The ...mentioning
confidence: 99%
“…This activation, in turn, stimulates TNFα and nerve growth factor (NGF) production by SCs themselves. TNFα overexpression is found in oral cancer tissues and is indeed correlated with elevated pain, while supernatants from activated SCs can increase facial allodynia in mice [ 59 ]. The TrkB/BDNF signalling axis is involved in the oral cancer PNI process, since modulation of this pathway in co-culture studies regulates SC—tumour cell interaction, and influences cell migration and differentiation [ 60 , 61 ].…”
Section: Schwann Cell Involvement In Physiology and Disorders Of The ...mentioning
confidence: 99%
“…Schwann cells are activated in the presence of pancreatic, colon, gastric, lung, skin, and oral cancer cells and promote cancer growth, invasion, and dispersion [11,52,[140][141][142][143][144][145][146][147][148][149]. Cancer-activated Schwann cells secrete neurotrophic factors, chemokines/cytokines, proteases, and adhesion molecules [52,143,146,147,149,150], many of which could directly excite and sensitize primary afferent neurons [151][152][153]. We and others recently found that Schwann cells and oral cancer cells reciprocally interact to promote each other's growth, migration, and invasion [52,147,152].…”
Section: Hncmentioning
confidence: 99%
“…Cancer-activated Schwann cells secrete neurotrophic factors, chemokines/cytokines, proteases, and adhesion molecules [52,143,146,147,149,150], many of which could directly excite and sensitize primary afferent neurons [151][152][153]. We and others recently found that Schwann cells and oral cancer cells reciprocally interact to promote each other's growth, migration, and invasion [52,147,152]. Besides, supernatant collected from oral cancer-activated Schwann cells produces a nociceptive response in mice [52].…”
Section: Hncmentioning
confidence: 99%